Characterization of mRNA isoform diversity in a transgenic model of tau pathology using targeted long‐read sequencing: Genetics/molecular genetics. (7th December 2020) - Leung, Szi Kay; Jeffries, Aaron; Hannon, Eilis; Castanho, Isabel; Moore, Karen; Murray, Tracey K.; Ahmed, Zeshan; Collier, David A.; Mill, Jonathan
Abstract: Background: An increasing number of studies implicate a role for alternative splicing in the development and neuropathology of Alzheimer's disease (AD). However, it has been historically challenging to characterise splicing events, due to the limitations of short‐read RNA‐sequencing (RNA‐Seq) for the capture full‐length transcripts critical for transcriptome assembly. In this study, we used Pacific Biosciences long‐read isoform sequencing (Iso‐Seq) to enrich and comprehensively characterise isoform diversity for AD‐associated genes in entorhinal cortex samples from a well‐validated AD transgenic mouse model. Method: We used Pacific Biosciences Targeted Iso‐Seq to investigate splicing of 20 AD‐associated genes (including TREM2, BIN1, and APOE ) in entorhinal cortex of a well‐characterised mouse model of tau pathology, rTg4510. Sequence data was processed using the Iso‐Seq3 pipeline, followed by downstream analysis using other publically available resources and customised scripts. The same samples have additionally been sequenced using whole transcriptome Iso‐Seq and RNA‐Seq as validation. Result: We obtained deep sequencing coverage of full‐length transcripts for each of the AD genes, revealing complex usage of alternative start sites and splicing events, as well as many novel 5′starts and 3'ends not previously annotated in existing genomic datasets. We identified differential transcript expression and isoform usage between transgenic and wild‐type mice, with highly‐correlated gene expression between Iso‐Seq and short‐read RNA‐seq data. Conclusion: This study highlights the application of long‐read sequencing approaches to assess splicing variation and isoform diversity in AD by selective gene enrichment. Results suggest differential splicing events associated with AD pathology, supporting a role for transcriptomic dysregulation in development of AD. Further work will be undertaken to characterise other AD‐associated genes, and to extend these analyses to human post‐mortem brain samples.